Evidence Law Curriculum System Construction Guided by Xi Jinping Thought on the Rule of Law - Wang, Wenhua (International Journal of Social Sciences and Public Administration, 2025)
As a core course in legal education and a crucial component of judicial practice, the theoretical development and pedagogical reform of Evidence Law must be rooted in the spirit of the times and the grand blueprint of national rule of law construction. Xi Jinping Thought on the Rule of Law, with its profound theoretical connotations and distinct practical orientation, provides the fundamental guidance and action plan for the construction and refinement of the Evidence Law system with Chinese characteristics. This article systematically elucidates the guiding role of Xi Jinping Thought on the Rule of Law in the theoretical construction of the Evidence Law curriculum system from four dimensions: the shaping of the core values of Evidence Law by the concept of "Fair Justice"; the concrete implementation of the principles of "Sound Laws and Good Governance" and "Justice for the People" in evidence rules; the guidance of the "Socialist Rule of Law Path with Chinese Characteristics" for the localization and innovation of evidence systems; and the methodological insights provided by "Systems Thinking" for the top-level design of Evidence Law. By integrating theory with classroom practice, we aim to construct an Evidence Law curriculum system that more closely aligns with the practical needs of China's rule of law and highlights Chinese characteristics, thereby contributing intellectual power to the cultivation of rule of law talent in the new era and the modernization of national governance capabilities.